Vaccination Status and Symptom Severity in Covid-19 Patients - Nisrina Anggraeni; Titik Kuntari (JURNAL INFO KESEHATAN, 2025)
We are still attempting to reduce COVID-19 morbidity and mortality through several means, including immunization. In early December 2021, Indonesia had 49.19% coverage of the second COVID-19 vaccination. Researching and collecting data on the association between vaccine completion and symptom severity is critical to persuade individuals to vaccinate. This study aims to examine the relationship between COVID-19 vaccination status and the degree of symptom severity in COVID-19 patients. This cross-sectional study used secondary data from the medical records of COVID-19 patients at the PDHI Yogyakarta Islamic Hospital from June to October 2021. The "PeduliLindungi" application was used to acquire vaccination status information. We used the chi-square test and multiple logistic regression for bivariate and multivariate analyses. The study enrolled 112 participants who met the criteria. The severity of COVID-19 symptoms was related to vaccination status and hypertension. Patients who were unvaccinated or had only partially vaccinated were 62.383 times more likely to develop severe and critical severity (aOR 62.383; 95% CI 12.129-320.861). Patients with hypertension were 3.643 times more likely than those without hypertension to experience severe or critical symptoms (aOR=3.643; 95% CI 1.025-12.952). Male gender, elderly age, chronic lung illness, and diabetes mellitus slightly increased the likelihood of severe symptoms but were not statistically significant. Complete immunization is strongly advised to reduce the risk of severe or critical symptoms.